The Early Chinese Empires : Qin and Han - Lewis, Mark Edward, 1954- (History of imperial China., 2007)
"In 221 bc the First Emperor of Qin unified the lands that would become the heart of a Chinese empire. Though forged by conquest, this vast domain depended for its political survival on a fundamental reshaping of Chinese culture. With this informative book, we are present at the creation of an ancient imperial order whose major features would endure for two millennia"--Publisher website (August 2007)